How to best conduct universal HIV screening in emergency departments is far from settled - Daniel J. Escudero; Monica Bahamon; Patricia Panakos; Daniel Hercz; George R. Seage III; Roland C. Merchant (Journal of the American College of Emergency Physicians Open)
Abstract HIV screening in the emergency department (ED), including universal screening irrespective of risk assessments, has shown strong promise in past studies, identifying many new cases of HIV infection among those who lack access to traditional HIV testing services. Yet, over the years a consistent set of challenges and limitations have presented themselves in settings throughout the United States. We review considerations for evaluating and improving the success of ED‐based HIV screening programs in the United States.